Lattice-gas Monte Carlo study of sI clathrate hydrates of ethylene: Stability analysis and cell distortion - Longone, Pablo Jesus (2020)
In this paper, a two-dimensional lattice-gas model is applied to study the stability and lattice distortion of sI clathrate hydrates of ethylene. Two levels of approximation are considered for the lateral interactions between the adsorbed molecules. By using Monte Carlo simulations, adsorption isotherm (coverage of the cavities as a function of the chemical potential), degree of deformation of the sI structure, and free energy of the adsorbed phase are obtained. A direct relationship between cell distortion and cell occupancy is observed. In addition, the minimum distortion coincides with the minimum value of the free energy. Accordingly, the stability phase diagram can be calculated from the values of the chemical potential at the minimum deformation. The obtained results indicate that the most stable condition of the system occurs for values of the cavity density ranging between 0.35 and 0.4. Finally, MC results are compared with data from experiments and more complex simulations.